Development of long-term financing of innovative small companies - N. I. Morozko; N. I. Morozko (Вестник университета)
The subject of the research is financial relations in the process of financing innovative small companies. The purpose of the work is an analytical assessment of the conditions for long-term financing of innovative small companies using systematic, economic and statistical analysis, which ensures the integrity and comprehensiveness of the study. Increasing the role of innovative small companies in the process of digital transformations is an urgent task in modern transformations of society. The analysis revealed the problems of long-term financing of innovative small companies, since most of the methods are focused on short-term financing of such companies. The conditions of investment opportunities for innovative companies are considered in detail on specific examples. The article notes that the conditions for effective management of long-term investments depend on the various stages of development of innovative companies. The practical purpose and scientific value of the article lies in the construction of a holistic and logical representation of the use of various methods of financing high-tech companies. It is concluded that it is necessary to provide institutional financial support for innovative development and an integrated approach to long-term financing of innovative small companies.